Multi-Locality Studies: Recent Insights and Future Pathways. Introduction to the Special Issue - Alberio, Marco; Caiello, Simone; Schlinzig, Tino (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2024)
Multi-Locality Studies: Recent Insights and Future Pathways. Introduction to the Special Issue